Rancang Bangun Alat Pengukur Suhu Real Time Laboratorium menggunakan Protokol MQTT Berbasis Internet of Things - Indrawata Wardhana; Vandri Ahmad Isnaini; Rahmi Putri Wirman; Rita Syafitri; Akhmad nasuha (Jurnal Teori dan Aplikasi Fisika, 2021)
The stable temperature in the laboratories is the major requirement for ensuring safety at work. The changes in the temperature which are oftentimes caused by precisely unrecognized factor may provide hazardous impacts on humans who are working in such place. Similar researches were conducted; however, they did not use NodeMCU as a microcontroller and MQTT protocol. This study tried to build a real-time temperature observation system using MQTT protocol based on the Internet of Things which has a fast delivery speed message. The temperature and humidity were captured by using DHT22 sensor that were then stored in database for one month. The result showed that the temperature change of the laboratory could be rapidly detected through the tests process on a certain heat-produced device. It could be analyzed periodically using the real-time application so that the impact of temperature rise could be detected quickly.